Efficacy Teacher In Embedding Discipline Student at Islamic Boarding School - Runiasih, Mawar; Nurhattati, Nurhattati; Kamaludin, Kamaludin (IJBLE Scientific Publications Community Inc., 2025)
This study aims to determine how much efficacy of Islamic Boarding School teachers in instilling discipline in students is supported by two constructs, namely social support and work engagement. Teacher efficacy is the belief and ability of a teacher in achieving success. One indicator of teacher efficacy is efficacy in discipline. Discipline is an indicator of student success. Therefore, instilling discipline in schools is very necessary to see student learning outcomes. The sample in this study were 32 Islamic Boarding School teachers with Stratified random sampling as a sampling technique. Data collection techniques using a questionnaire with a Likert scale. The data analysis technique in this study used SPSS version 22. The results of this study were for the Social Support (SS) variable to obtain a Chi-Square value of 9.120 with a significance value of 0.000. Work Engagement (WE) obtained a Chi-Square value of 44.970 with a significance value of 0.000. And Teacher Efficacy (TE) obtained a Chi-Square value of 7,179 with a significance value of 0.410.